Voltage Support Experimental Analysis of a Low-Voltage Ride-Through Strategy Applied to Grid-Connected Distributed Inverters - Miguel Garnica; Luís García de Vicuña; Jaume Miret; Antonio Camacho; Ramón Guzmán (Energies, 2018)
In recent decades, different control strategies have been designed for the increasing integration of distributed generation systems. These systems, most of them based on renewable energies, use electronic converters to exchange power with the grid. Capabilities such as low-voltage ride-through and reactive current injection have been experimentally explored and reported in many research papers with a single inverter; however, these capabilities have not been examined in depth in a scenario with multiple inverters connected to the grid. Only few simulation works that include certain methods of reactive power control to solve overvoltage issues in low voltage grids can be found in the literature. Therefore, the overall objective of the work presented in this paper is to provide an experimental analysis of a low-voltage ride-through strategy applied to distributed power generation systems to help support the grid during voltage sags. The amount of reactive power will depend on the capability of each inverter and the amount of generated active power. The obtained experimental results demonstrate that, depending on the configuration of distributed generation, diverse inverters could have different control strategies. In the same way, the discussion of these results shows that the present object of study is of great interest for future research.